Surveillance Video Pixel Analysis Via Block-Based Pixel Subtraction Technique - Sarban Singh, Ranjit Singh; Anas, Siti Aisyah; Tan, Chee Fai; Hashim, Nik Mohd Zarifie (2012)

(untitled)
Video is constructed based on sequence of frames which conveys different type of information based on the pixels values. Information of each frame changes from one frame to another frame which also is based on pixels values. These changes are referred as motion translation. This motion translation can be analyzed wit11 comparing or subtracting both the current frame and subsequent frame pixels values. In this paper, a study is conducted to analyze the motion translation using the pixel subtracting technique. A video is processed to extract all the frames into sequences. Two targeted frames are selected from the extracted sequences of frames to be analyzed for motion translation. The two selected frames are divided into I6 x 16 block size for data analysis purposes. This technique is a fast and reduces the processing time due to only pixels values difference is analyzed for data processing purposes. It also saves memory space because it only involves values subtraction.